Democratisation under diversity: Theory and evidence from Indonesian communities - Anirban Mitra; Sarmistha Pal (University of Kent, School of Economics, 2020)
We study the effect of ethnic diversity on local public spending following fiscal decentralisation in a setting where local institutions condition cooperative behaviour across ethnic groups. The theory we develop highlights the role of the local elite in lobbying for policies which favour them in a decentralised setting. The differences in preferences over public good allocations along with the salience of coordination costs across ethnic groups are relevant in determining the equilibrium lobbying behaviour. This results in ethnic diversity having a detrimental effect on local developmental spending which is aggravated by increased levels of coordination costs. We test these predictions using Indonesian community-level data. Utilising the 1997 and 2007 Indonesian Family Life Survey (IFLS) rounds, we are able to construct various measures of ethnic diversity. Also, we exploit an institutional feature of Indonesian communities - namely, the observance of traditional "Adat" laws to proxy coordination costs across ethnic groups. Overall, we find that ethnic diversity depresses local development spending post-decentralisation at the community level particularly where Adat laws are not followed, which is consistent with our theory.
Keywords: D72; D74; H40; 330; Decentralisation; Lobbying; Local development; Political Economy